Sestava, lastnosti, uporaba in reciklaža Kerrocka - Vovk, Matej (Les (Ljubljana), 2017)
Kerrock is a solid surface composite material, which is composed of 40 wt.% of polymethylmethacrylate (PMMA) and 60 wt.% of aluminium trihydroxide (ATH) filler with silane as a coupling agent. Similar material is also called PMMA/ATH composite in the academic literature, while Kerrock is one of its commercial names. PMMA is a hard material that is water- and UV-resistant and easy to work with, although its characteristics depend on the degree and process of polymerization that occurs. ATH is a white, nontoxic material that is relatively soft and non-abrasive. It is widely used as an effective fire-retardant filler in polymer composites. Because of its composition, the machining of Kerrock is similar to the machining of wood. Moreover, it can also be thermoformed, like thermoplastics. Kerrock is widely used for work surfaces and cladding, with both indoor and outdoor applications. The material%s interfacial morphology, interfacial adhesion between the filler and polymer matrix, dispersion of ATH particles and concentration of adhesion promoting agent have the biggest impacts on the mechanical characteristics of Kerrock. While it is possible to chemically recycle Kerrock, the energy required for this is too high for this process to be practical. Another option for recycling this composite is to combine its particles in a hot press or to add MMA or polyester resin before pressing. However, there remains much work to be done with regard to effectively recycling Kerrock
Keywords: ATH; composite; Kerrock; kompozit; PMMA; PMMA/ATH; reciklaža; recycling; silan; silane